Effect of Drought Stress During Flowering Stage on Starch Accumulation and Starch Synthesis Enzymes in Sorghum Grains - Bing YI; Yu-fei ZHOU; Ming-yue GAO; Zhuang ZHANG; Yi HAN; Guang-dong YANG; Wenjuan XU; Rui-dong HUANG (Journal of Integrative Agriculture, 2014)
Starch content is a key factor affecting sorghum grain quality. The research of sorghum grain starch accumulation and the related synthesis enzyme activities has great significance for understanding the mechanisms of starch metabolisms. The differences between a high and a low starch content sorghum hybrids (Tieza 17 and Liaoza 11, respectively) in grain starch accumulation and the related synthesis enzyme activities were assessed following imposition of water stress during flowering stage. The total starch, amylase and amylopectin accumulation all decreased at the mid-late stage of grain filling under drought stress during flowering stage. The maximum and mean accumulation rates also decreased. During grain filling, soluble starch synthase (SSS), granule-bound starch synthase (GBSS), starch branching enzyme (SBE), and starch debranching enzymes (DBE) activities were all affected, though differently. Drought stress reduced starch accumulation in a larger extent for Tieza 17 than Liaoza 11. Drought stress during flowing stage reduced starch synthesis enzyme activities, thus reducing starch accumulation in grains, and the differences between starch components were also demonstrated under drought stress.